Impacto en la comercialización de la producción de pollos Broilers y su relación con la economía ecuatoriana - Santana Zuñiga, Nayely Anthonella (2024)
The breeding and management of Broiler chicken production is of utmost importance, for what concerns the commercialization and profitability of our country, since the demand for the consumption of chickens here in Ecuador is very high. However, the sustainability and competitiveness of this industry face increasing challenges, from fluctuations in prices of inputs and final products to changes in national and international market demand. Therefore, the objective of this study focuses on analyzing the commercialization of broiler chicken production in the context of the Ecuadorian economy. Therefore, in this study a deductive-descriptive approach was used, through an extensive review of the literature used in document analysis. The results have determined that the cost of production of broiler chickens in Ecuador is a combination of several factors that influence the profitability of this industry, the main cost components include feed since this can represent up to 70% of the total cost of production. production. Finally, it was concluded that the high costs of inputs such as feed and fluctuations in market prices represent significant obstacles that can limit the ability of producers to achieve consistent profit margins and affect the economic stability of the poultry sector.